2020
DOI: 10.1159/000512011
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cytology in the Current Guidelines for Malignant Mesothelioma: Largest Study from India

Abstract: <b><i>Introduction:</i></b> Cytology provides crucial window for early diagnosis of malignant mesothelioma (MM) since it is often the first and easily available material for evaluation, resulting in early treatment. Still, its role is overlooked in the current treatment guidelines. The aim of this study is to determine the sensitivity of cytomorphology and role of subsequent ancillary techniques in diagnosing MM. <b><i>Methods:</i></b> This is a 5-year retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…ICC has been shown to have superior staining results in cell blocks compared to conventional smears and LBC specimens. 9,[13][14][15] In this study, we prepared cell blocks from cells pretreated with an LBC fixative solution and cell blocks from LBC residual specimens. Our preliminary experiments showed that the immunostaining of cells treated with LBC fixative was lower than that of cells fixed with 10% NBF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICC has been shown to have superior staining results in cell blocks compared to conventional smears and LBC specimens. 9,[13][14][15] In this study, we prepared cell blocks from cells pretreated with an LBC fixative solution and cell blocks from LBC residual specimens. Our preliminary experiments showed that the immunostaining of cells treated with LBC fixative was lower than that of cells fixed with 10% NBF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, morphological approaches are limited, and ICC, FISH, and nucleic acid sequence analyses using DNA and RNA extraction are useful. ICC has been shown to have superior staining results in cell blocks compared to conventional smears and LBC specimens 9,13–15 . In this study, we prepared cell blocks from cells pretreated with an LBC fixative solution and cell blocks from LBC residual specimens.…”
Section: Discussionmentioning
confidence: 99%
“…This reporting may be due to the smaller numbers, as compared to other cancers, but this rarity cannot be considered as absence of mesothelioma in India. On the other hand, in another study, which is stated by its authors to be the ‘largest study from India’ on malignant mesothelioma, the proven cases from 2015 to 2019 in the archives of the Department of Onco-pathology at Gujarat Cancer Research Institute were 128 10 .…”
Section: Introductionmentioning
confidence: 95%